The effects of tapering and artery wall stiffness on treatments for Coarctation of the Aorta. Issue 14 (26th October 2017) - Pathirana, Dilan; Johnston, Barbara; Johnston, Peter
Abstract: Coarctation of the Aorta is a congenital narrowing of the aorta. Two commonly used treatments are resection and end-to-end anastomosis, and stent placements. We simulate blood flow through one-dimensional models of aortas. Different artery stiffnesses, due to treatments, are included in our model, and used to compare blood flow properties in the treated aortas. We expand our previously published model to include the natural tapering of aortas. We look at change in aorta wall radius, blood pressure and blood flow velocity, and find that, of the two treatments, the resection and end-to-end anastomosis treatment more closely matches healthy aortas.